Identification of the interacting proteins of Bambusa pervariabilis × Dendrocalamopsis grandis in response to the transcription factor ApCtf1β in Arthrinium phaeospermum - Yan, Peng; Yu, Jiawen; Fang, Xinmei; Li, Shuying; Han, Shan; Lin, Tiantian; Liu, Yinggao; Yang, Chunlin; He, Fang; Zhu, Tianhui; Li, Shujiang (Frontiers in Plant Science, 2022)
Arthrinium phaeospermum is the main pathogen that causes Bambusa pervariabilis × Dendrocalamopsis grandis blight. It secretes the cutinase transcription factor ApCtf1β, which has been shown to play an important role in B. pervariabilis × D. grandis virulence. However, knowledge about the interaction target genes of ApCtf1β in B. pervariabilis × D. grandis remains limited. A cDNA library for the yeast two-hybrid system was constructed from B. pervariabilis × D. grandis shoots after 168 h treatment with A. phaeospermum. The library was identified as 1.20 × 107 cfu, with an average insert > 1000 bp in size and a 100% positive rate, providing a database for the subsequent molecular study of the interaction between A. phaeospermum and B. pervariabilis × D. grandis. The yeast two-hybrid (Y2H), bimolecular fluorescence complementation (BiFC), and glutathione-S-transferase (GST) pull-down assays were used to screen for and identify two ApCtf1β interacting target proteins, BDUbc and BDSKL1, providing a reliable theoretical basis to study the molecular mechanism underlying B. pervariabilis × D. grandis resistance in response to A. phaeospermum, which would, in turn, establish a platform to develop new strategies for the sustainable and effective control of the blight diseases of forest trees.